2013
DOI: 10.3389/fimmu.2013.00128
|View full text |Cite
|
Sign up to set email alerts
|

Prime-Boost Strategies in Mucosal Immunization Affect Local IgA Production and the Type of Th Response

Abstract: Combinations of different delivery routes for priming and boosting represent vaccination strategies that can modulate magnitude, quality, and localization of the immune response. A murine model was used to study T cell clonal expansion following intranasal (IN) or subcutaneous (SC) priming, and secondary immune responses after boosting by either homologous or heterologous routes. T cell primary activation was studied by using the adoptive transfer model of ovalbumin-specific transgenic CD4+ T cells. Both IN an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 43 publications
5
54
0
Order By: Relevance
“…Intranasal priming in particular has been shown to influence stronger Th1 polarization along with a higher local IgA response [42]. Similarly, mice receiving either an intranasal prime or boost were shown to also produce higher levels of IL-17A [42]. We saw a robust antigen specific gut IgA response, which can be a major advantage in the context of vaccines against enteric pathogens.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Intranasal priming in particular has been shown to influence stronger Th1 polarization along with a higher local IgA response [42]. Similarly, mice receiving either an intranasal prime or boost were shown to also produce higher levels of IL-17A [42]. We saw a robust antigen specific gut IgA response, which can be a major advantage in the context of vaccines against enteric pathogens.…”
Section: Discussionmentioning
confidence: 79%
“…Mucosal immunization has been shown to elicit both local and systemic humoral as well as cellular responses in animal models and in humans [41]. Intranasal priming in particular has been shown to influence stronger Th1 polarization along with a higher local IgA response [42]. Similarly, mice receiving either an intranasal prime or boost were shown to also produce higher levels of IL-17A [42].…”
Section: Discussionmentioning
confidence: 99%
“…The priming and boosting strategy is demonstrated to be required to establish optimal T cell immunity. 21 However, current human inactivated influenza vaccines are given through intradermal or intramuscular injection, and thus fail to generate robust anti-influenza T cell immunity in the lung. It has been shown that the local boosting strategy can help establish robust memory T cells in peripheral tissues.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the local boosting strategy can help establish robust memory T cells in peripheral tissues. [21][22][23] In addition, robust resident T cell immunity in lung is critical to protect from acute influenza viral infection. [24][25][26] Nevertheless, little is known about the effects of pulmonary boosting vaccines with adjuvants on local development of antigen-specific Treg cells in lung.…”
Section: Introductionmentioning
confidence: 99%
“…The factors which favor development of mucosal immune responses include the mucosal or trans cutaneous immunization and the replicating nature of the vaccine agents [84,85]. A prime boost strategy with heterologous routes of administration based on the combination of mucosal and parenteral delivery has been attempted in a murine model for inducing immune responses at both mucosal and systemic levels [86]. Although mucosal route for vaccination is desired for its ease of administration and development of local immunity, mucosal vaccinations are faced with safety concerns and problems of lesser efficacy [87].…”
Section: Site Of Immune Responsementioning
confidence: 99%